A case report of nasal lobular capillary hemangioma and its management - K., Vybhavi M.; V., Srinivas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Nasal lobular capillary hemangioma is a benign vascular lesion marked by epistaxis and nasal obstruction. The nasal cavity is a relatively rare location as lobular capillary hemangiomas commonly occur in the oral cavity. They are termed as lobular capillary hemangioma based on the histopathological features of anastomosing capillary networks arranged in lobular architechture. We report a case of 40 year old female with history of left nasal obstruction and recurrent epistaxis since 2 months. Examination of nose revealed a protruding reddish coloured mass on the left side and CT scan of nose and paranasal sinuses showed the mass arising from the anterior part of nasal septum along with nasal spur. Patient underwent surgical excision of the mass along with spur removal under general anesthesia. Histopathology demonstrated vascular proliferative lesion consistent with hemangioma. The diagnosis of capillary hemangioma must always be taken into account while considering the differential diagnosis of bleeding mass in the nasal cavity.